Internet-Based Cognitive Behavior Therapy Only for the Young? A Secondary Analysis of a Randomized Controlled Trial of Depression Treatment - Pabst, Alexander; Löbner, Margrit; Stein, Janine; Luppa, Melanie; Kersting, Anette; König, Hans-Helmut; Riedel-Heller, Steffi G. (Frontiers in Psychiatry, 2020)
Background: Late-life depression is a major public health concern, driving the development of complementary treatment options. This study investigates the effectiveness and acceptability of internet-based Cognitive Behavioral Therapy (iCBT) in older individuals (60+ years) compared to younger age groups. Materials and Methods: Secondary analysis of a cluster-randomized controlled trial with 647 (18-82 years; mean 43.9) mildly to moderately severe depressed primary care patients receiving either iCBT + treatment as usual (TAU) or TAU alone. Severity of depression was measured by the Beck Depression Inventory (BDI-II) at baseline, 6 weeks and 6 months. Intention-to-treat-analysis in three age groups (18-39 years, n = 264; 40-59 years, n = 300; 60+ years, n = 83) was performed, using mixed-effects regression models to quantify treatment effect. Results: No age differences in the effectiveness of iCBT were found. Patients in the intervention group consistently showed a greater reduction in depression severity than controls in all three age groups and at both follow-ups. Effect sizes ranged from d = 0.31 (40-59 years, 6 weeks) to d = 1.71 (60+ years, 6 months). Uptake of the intervention was banded around 70% with no differences between age groups (χ² = 0.18, p = .915). The mean number of completed modules increased with age (χ² = 18.99, p = .040). Discussion: iCBT is equally effective in both younger and older individuals, thus providing a valuable complementary element of routine late-life depression care.